AB1308 Factors associated with the development of esrd in a recent large single centre cohort of patients with lupus nephritis. (12th June 2018) - Dasilva Santos, I.; Wilson, H.; Turner-Stokes, T.; Cairns, T.; Lightstone, L.
Abstract : Background: Lupus nephritis (LN) remains a major cause of morbidity in systemic lupus erythematosus. Worldwide, at 5 years about 19% (Class IV) and 4% (class V) of patients with LN develop end-stage renal disease (ESRD), depending upon the disease severity, ancestral and socio-economic factors as well as response to initial treatment. ESRD is an unusual direct cause of death in this disease but is associated with premature mortality. Objectives: The aim of this study was to retrospectively review our large cohort of LN patients, predominantly treated with MMF and rituximab based steroid sparing regimens, who required renal biopsy for new presentation between 2010 and 2017 to analyse the factors associated with the development of ESRD. Methods: We identified 176 patients with LN from a renal biopsy database, at our tertiary Lupus Centre presenting between 01/2010 and 09/2017. The 21 patients (11%) who progressed to ESRD were included, and using propensity score matching, were matched for age, gender and ethnicity with 63 patients who did not develop ESRD. Patients who required dialysis at presentation were excluded. Results: Baseline characteristics were similar with regard to gender, age and ethnicity between both groups. Mean follow-up was 4±17 years overall (2.1±1.4 years in the ESRD group and 3.8±1.5 years in the non-ESRD group, p=0.0002). The ESRD group had significantly higher serum creatinine at baseline (184.2±143.6 vs 89.0±48.0, p=0.031) and and at 12 m (256.2 vs 79.5, p=0.001) and significantly lower baseline eGFR (44.6 vs 68.1, p=0.003) and eGFR at 12 m (27 vs 73.1, p=0.001). The absence of remission at 1 year was also associated with a higher risk of ESRD (71.7% vs 9.5%, p=0.001), as well as the presence of positive MPO-ANCA (p=0.040), the ANCA titre (p=0.031) and persistent low levels of complement (50% vs 21.5%, p=0.035). Using multivariable regression analysis, independent factors predictive of ESRD were baseline serum creatinine and no response to treatment at 12 months. There was no significant difference in outcome between groups regarding the type of induction treatment. Conclusions: The rates of ESRD in our LN cohort are comparable with the published literature despite. In our patient population with high use of rituximab and low steroids, the features that predict poor long term outcome are baseline serum creatinine and the failure to attain a remission at 1 year. These data highlight the importance of a) early diagnosis of lupus nephritis and b) defining the features which determine non response at 1 year and being able to identify earlier what would be the right treatment regimen for each individual patient. References: [1] Hanly JG, et al. Rheumatology (Oxford)2016; 55: 252–262. [2] Korbet SM, et al. Am J Kidney Dis2000; 35: 904–914. [3] Tektonidou MG, et al. Arthritis Rheumatol. 2016; 68(6):1432–4. [4] Ortega LM, et al. Lupus. 2010;19(5):557. Disclosure of Interest: None declared